The lateral and vertical limits of a hypothetical Republic of South Africa continental shelf according with international law and, in particular, Articles 76, 83 and 84 of the United Nations Law of the Sea Convention (1982) - Guy, Neil Raymond (Institute of Marine and Environmental Law, 2023)
Coastal States have laid claim, progressively, to the sea areas adjoining them found until recent times these claims have been, ostensibly, to ensure the security of the State and the right to harvest the potential of the sea. It is obvious that foreign vessels, close to the coast of a State, could constitute a threat and in the past, as the dangers of improved weaponry became apparent, some coastal States felt the need to extend their territory still further seawards. However, the most significant claims to extended sovereignty have been in recent times, as a result of the efforts of coastal States to control the newly discovered potential of the seabed, and in particular, the continental shelf. As technology improves, the possibility of exploiting sea-bed resources will extend further and further seawards to the point where, in time, it will be possible to harvest and mine all of the seabed, regardless of depth. It should be noted that some States have extended their claims to a limit that the international community will not accept. An example oftJ,;s is the 200 nautical mile(nm) territorial waters claims of Argentina in 1966 and Brazil in 1970. Argentina has subsequently adjusted its claim to conform with the articles of the Law of the Sea Convention of 1982 LOSC. (1) Vast changes in the type and quantity of potentially hazardous substances, that are being transported by sea, such as crude oil, nuclear waste, chemicals, etc, have also brought with them an ever-increasing threat of pollution. To prevent the destruction of their resources, coastal States are also taking more stringent measures in the seas surrounding them. To illustrate this threat, during the period 1950 to 1975, the dead-weight tonnages of crude-oil tankers increased from an average of 30 000 to 500 000 tonnes and the draughts (depths) of these vessels increased from 10 metres to about 30 metres when loaded. This marked increase in size and draught of vessels could mean that the information on navigational hazards is inadequate for their safe passage. This has increased both the possibility of accidents and the gravity of the consequences of such accidents, thus making it urgent for coastal States to control their seaward territories and zones. It is the intention to consider all aspects of international law and marine-geological factors that could affect continental shelf claims of the Republic of South Africa (RSA). To be able to do this satisfactorily it is necessary to consider international treaties, conventions, judgements in international disputes and the practice of States that could be regarded as customary law. As some of the criteria used in international law to claim continental shelf depend on the geological configuration of the continental shelf of a coastal State it is necessary to consider geological concepts in general and the history of the shelf of the RSA in particular. It is anticipated that in some areas insufficient data will be available to finalise a claim and it is the intention also, therefore, to identify these areas and the data required for a comprehensive and internationally acceptable claim to be made. The deep-sea bed is being explored for possible exploitation, but the ownership of deep-sea resources was not satisfactorily regulated in international customary law. LOSC, adopted in J 982, has not been ratified by the major and most powerful coastal States. This is in spite of attending States to the Conference endeavouring at great length to resolve the problems. This is most likely due to the Articles in the Convention dealing with exploration and exploitation of the deep-sea bed. Of the resources found on the continental shelf, as defined in LOSC, extensive oil and gas reserves phosphorites, manganese nodules and diamonds make up more than 90% of the value of the total. Some of the lesser important resources include sand and gravel, titanium, tin, chromium, and zirconium. Pools of brine contain concentrations of lead, zinc, gold and silver and it must be accepted that advancing technology will eventually make these resources economically viable propositions. Continental shelf claims beyond any exclusive economic or fishing zones include sedentary species such as oysters, clams, lobsters and ~rabs, which could in some areas such as the Pacific Ocean become an important consideration for exploitation. The requirements for acceptable international standards of delineation of the continental shelf have not evolved through international customary Jaw, because there has been little if any reason for a coastal State to give serious thought to the exploitation of the land under the sea until the middle of the 20th century. The Convention on the Continental Shelf adopted in Geneva in 1958 was the first real effort, on an international scale, to draw up Convention rules capable of resolving the overlapping claims of States. (This convention is usually known as CSC, but to avoid confusion, it will be referred to as CSC58). This convention did not clarify the complexities of continental shelf or margin claims and the problem was further considered during the drafting of LOSC. In spite of the fact that major coastal States have not ratified this Convention most have, nevertheless, laid claim to areas of the continental shelf and to the exploration of the potential of the resources of the deep-sea bed. The criteria laid down in LOSC to delineate continental shelf claims include limits that could be determined ' from bathymetric records, from seismic reflection or refraction profiles of the margin and also from the ratio of sediment thickness to the distance of that sediment position to the foot of the slope.